A Survey of Mammal and Fish Genetic Diversity Across the Global Protected Area Network - Schmidt, Chloé; Karachaliou, Eleana; Vandergast, Amy G.; Crandall, Eric D.; Falgout, Jeff; Hunter, Margaret E.; Kershaw, Francine; Leigh, Deborah M.; O'Brien, David; Paz‐Vinas, Ivan; Segelbacher, Gernot; Garroway, Colin J. (Conservation letters, 2025)
ABSTRACT Global conservation targets aim to expand protected areas and maintain species’ genetic diversity. Whether protected areas capture genetic diversity is unclear. We examined this question using a global sample of nuclear population‐level microsatellite data comprising genotypes from 2513 sites, 134,183 individuals, and 176 mammal and marine fish species. The genetic diversity and differentiation of samples inside and outside protected areas were similar, with some evidence for higher diversity in protected areas for small‐bodied mammals. Mammal populations, particularly large species, tended to be more genetically diverse when near multiple protected areas, regardless of whether samples were collected in or outside protected areas. Older marine protected areas tended to capture more genetically diverse fish populations. However, limited data availability in many regions hinders the systematic incorporation of genetic diversity into protected area design. Focusing on minimizing population decline and maintaining connectivity between protected areas remain essential proxies for maintaining genetic diversity.